Strategi Kepala Sekolah dalam Meningkatkan Kualitas Pendidik - Hairul Huda; Yudin Citriadin; Nurul Yakin; Miskan Miskan (Universitas Muhammadiyah Mataram, 2025)
Abstract: School principals play a strategic role in determining the direction and quality of education in schools, including efforts to improve the quality of educators. This study aims to analyze the strategies implemented by school principals to enhance the quality of teaching staff. A qualitative approach with a case study design was employed. The primary data sources consisted of the principal, vice principals, and teachers, totaling 23 informants. Data were collected through interviews, observations, and documentation. The data were analyzed using the theories of Miles, Huberman, and Saldaña. The validity of the data was ensured through credibility, dependability, confirmability, and transferability checks. The study results indicate that the main strategies implemented involve visionary leadership, human resource development, improvement of infrastructure and facilities, effective curriculum management, building a positive school culture, stakeholder engagement, as well as continuous evaluation and development. Specifically, the principal’s strategic implementation to improve educator quality was carried out through professional training and development programs, mentoring and supervision, teacher collaboration, provision of learning resources and technology, providing motivation and recognition, and encouraging continuous education. The consistent and adaptive application of these strategies in response to global dynamics is considered capable of creating a productive learning environment, producing professional educators, and graduating competitive students in the era of globalization.Abstrak: Kepala sekolah memiliki peran strategis dalam menentukan arah dan mutu pendidikan di sekolah, termasuk dalam upaya meningkatkan kualitas pendidik. Penelitian ini bertujuan untuk menganalisis strategi kepala sekolah dalam meningkatkan kualitas pendidik. Menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Sumber data primer adalah kepala sekolah, wakil kepala sekolah, dan guru-guru dengan jumlah informan sebanyak 23 orang. Data dikumpulkan dengan wawancara, observasi dan dokumentasi. Dianalisis menggunakan teori Milles, Huberman dan Saldana. Pengecekan keabsahan dengan credibility, dependability, confirmability, transferability. Hasil kajian menunjukkan bahwa strategi utama yang diterapkan meliputi kepemimpinan visioner, pengembangan sumber daya manusia, peningkatan sarana dan prasarana, pengelolaan kurikulum yang efektif, pembangunan budaya sekolah yang positif, pelibatan stakeholder, serta evaluasi dan pengembangan berkelanjutan. Secara khusus, implementasi strategis kepala sekolah dalam meningkatkan kualitas pendidik dilakukan melalui program pelatihan dan pengembangan profesional, pendampingan dan supervisi, kolaborasi antar guru, penyediaan sumber belajar dan teknologi, pemberian motivasi dan penghargaan, serta mendorong pendidikan berkelanjutan. Penerapan strategi-strategi tersebut secara konsisten dan adaptif terhadap dinamika global dinilai mampu menciptakan lingkungan belajar yang produktif, menghasilkan tenaga pendidik yang profesional, serta lulusan yang kompetitif di era globalisasi.